2020
DOI: 10.1101/2020.03.26.007559
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Action enhances predicted touch

Abstract: It is widely believed that predicted action outcomes are perceptually attenuated. The present experiments determined whether predictive mechanisms in fact generate attenuation, or instead enhance perception -via neural 'sharpening' mechanisms assumed to operate in sensory cognition domains outside of action. We manipulated probabilistic expectations in a force judgement task. Participants produced actions and rated the intensity of concurrent tactile forces. Experiment 1 confirmed previous findings that action… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 78 publications
(188 reference statements)
0
15
2
Order By: Relevance
“…In contrast, the active inference account can sufficiently explain the tactile gating effect; i.e., the reduction in the precision of somatosensory input on the moving limb during the movement. A recent study 64 suggested that action prediction does not produce somatosensory attenuation but enhancement and argued that the attenuation observed in all earlier experiments is actually due to nonpredictive gating processes. This claim cannot be supported based on several observations and arguments.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, the active inference account can sufficiently explain the tactile gating effect; i.e., the reduction in the precision of somatosensory input on the moving limb during the movement. A recent study 64 suggested that action prediction does not produce somatosensory attenuation but enhancement and argued that the attenuation observed in all earlier experiments is actually due to nonpredictive gating processes. This claim cannot be supported based on several observations and arguments.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study 64 suggested that action prediction does not produce somatosensory attenuation but enhancement and argued that the attenuation observed in all earlier experiments is actually due to nonpredictive gating processes. This claim cannot be supported based on several observations and arguments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Such suppression mechanisms are thought to attenuate tactile sensations during action regardless of whether they are predicted effects of action or not and are thought to be mediated by spinal mechanisms (Seki & Fetz, 2012), and comparable mechanisms may similarly attenuate sensory processing in a non-predictive fashion across modalities in humans and other animals (Crapse & Sommer, 2008). Importantly, recent experiments in touch suggest that when confounds related to sensory suppression are removed, action predictions may influence perception in a qualitatively similar fashion irrespective of sensory modality (Thomas, Yon, de Lange & Press, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…1a). These accounts share a family resemblance to Bayesian models of perception 9,[12][13][14] , which assume it is adaptive for sensory representations to be weighted towards predicted outcomesmaking us more likely to see, hear or feel sensory events that we expect to occur [15][16][17][18] . Analogously to Bayesian of models of perception, Bayesian models of metacognition suggest that top-down predictions 'sharpen' internal representations of expected events, leading to more sensitive metacognition about predicted signals 11,19 .…”
Section: Introductionmentioning
confidence: 99%